Circadian-based Treatment Strategy Effective in the BACHD Mouse Model of Huntington's Disease. Issue 5 (October 2018) - Whittaker, Daniel S.; Loh, Dawn H.; Wang, Huei-Bin; Tahara, Yu; Kuljis, Dika; Cutler, Tamara; Ghiani, Cristina A.; Shibata, Shigenobu; Block, Gene D.; Colwell, Christopher S.
Huntington's disease (HD) patients suffer from progressive neurodegeneration that results in cognitive, psychiatric, cardiovascular, and motor dysfunction. Disturbances in sleep-wake cycles are common among HD patients with reports of delayed sleep onset, frequent bedtime awakenings, and excessive fatigue. The BACHD mouse model exhibits many HD core symptoms including circadian dysfunction. Because circadian dysfunction manifests early in the disease in both patients and mouse models, we sought to determine if early interventions that improve circadian rhythmicity could benefit HD symptoms and delay disease progression. We evaluated the effects of time-restricted feeding (TRF) on the BACHD mouse model. At 3 months of age, the animals were divided into 2 groups: ad lib and TRF. The TRF-treated BACHD mice were exposed to a 6-h feeding/18-h fasting regimen that was designed to be aligned with the middle (ZT 15-21) of the period when mice are normally active (ZT 12-24). Following 3 months of treatment (when mice reached the early disease stage), the TRF-treated BACHD mice showed improvements in their locomotor activity and sleep behavioral rhythms. Furthermore, we found improved heart rate variability, suggesting that their autonomic nervous system dysfunction was improved. On a molecular level, TRF altered the phase but not the amplitude of the PER2::LUC rhythms measured in vivo and in vitro. Importantly, treated BACHD mice exhibited improved motor performance compared with untreated BACHD controls, and the motor improvements were correlated with improved circadian output. It is worth emphasizing that HD is a genetically caused disease with no known cure. Lifestyle changes that not only improve the quality of life but also delay disease progression for HD patients are greatly needed. Our study demonstrates the therapeutic potential of circadian-based treatment strategies in a preclinical model of HD.